Multilevel evidence of MECP2-associated mitochondrial dysfunction and its therapeutic implications - Balicza, Peter; Gezsi, Andras; Fedor, Mariann; Sagi, Judit C.; Gal, Aniko; Varga, Noemi Agnes; Molnar, Maria Judit (Frontiers in Psychiatry, 2024)
We present a male patient carrying a pathogenic MECP2 p.Arg179Trp variant with predominant negative psychiatric features and multilevel evidence of mitochondrial dysfunction who responded to the cariprazine treatment. He had delayed speech development and later experienced severe social anxiety, learning disabilities, cognitive slowing, and predominant negative psychiatric symptoms associated with rigidity. Clinical examinations showed multisystemic involvement. Together with elevated ergometric lactate levels, the clinical picture suggested mitochondrial disease, which was also supported by muscle histopathology. Exploratory transcriptome analysis also revealed the involvement of metabolic and oxidative phosphorylation pathways. Whole exome sequencing identified a pathogenic MECP2 variant, which can explain both the dopamine imbalance and mitochondrial dysfunction in this patient. Mitochondrial dysfunction was previously suggested in classical Rett syndrome, and we detected related phenotype evidence on multiple consistent levels for the first time in a MECP2 variant carrier male. This study further supports the importance of the MECP2 gene in the mitochondrial pathways, which can open the gate for more personalized therapeutic interventions. Good cariprazine response highlights the role of dopamine dysfunction in the complex psychiatric symptoms of Rett syndrome. This can help identify the optimal treatment strategy from a transdiagnostic perspective instead of a classical diagnostic category.